Teachers’ attitudes towards the amendments in the Design curriculum: a critical overview of the approach and findings of the study - Van Deventer, Anriet; Steyn, Raïta (Design and Technology Education: An International Journal, 2022)
This article[1] refers to the South African Design teachers’ attitudes towards the implementation of the 2020 Section 4 amendments of the Design Curriculum and Assessment Policy Statement (CAPS). The purpose of the article is twofold: first to establish the necessity for awareness of the teachers’ attitudes towards curriculum changes, especially when they are unexpected and abrupt. Secondly, to demonstrate the importance of awareness among educational authorities about the role of transparent discussions on the nature, purpose, and consequences of their relevant decisions before their final implementation. To this end, the article discusses the amendments and their differences to the former curriculum. The role of the Design teachers’ positive attitude towards curriculum changes, especially in dealing with challenging pedagogical issues and communicating creative motivation to learners, is critically assessed. Theoretically, the study was guided by Ubuntu philosophy and the South African democratic principles while methodologically, based on a qualitative data collection process, the attitudes of Design teachers from seven selected schools have been individually examined. In conclusion, the teachers’ heterogeneous responses have indicated that their opinions do not reflect the à priori governmental acceptance of the amendments. [1] The article is based on the PhD thesis by Anriët Van Deventer, under the title: ‘Teacher engagement with the process in Design: policies, problems, and visions’, submitted at the University of Pretoria in November 2021.